Naphthalocyanine thin films and field effect transistors - Esmail, Ayad M.S.; Staddon, Christopher R.; Beton, Peter H. (American Chemical Society, 2016)
Naphthalocyanine (Nc) thin films have been grown by sublimation on SiO2. We have used atomic force microscopy and X-ray diffraction to show that the films are disordered for room temperature deposition, but show a highly crystalline needlelike morphology for a substrate temperature of ∼200 °C. Field effect transistors exhibit p-channel operation with a mobility, which has a peak value of 0.052 cm2/(V s), showing a high dependence on substrate temperature. Exposure to atmosphere results in an increase in current and mobility and a reduction in threshold voltage. We compare our results with films formed from analogue molecules such as phthalocyanines and naphthalocyanine functionalized with solubilizing side groups and discuss the potential of Nc for applications in organic electronics and sensors.